DETERMINAN FINANCIAL SUSTAINABILITY RATIO BANK UMUM SYARIAH DI INDONESIA (ANALISIS DATA PANEL TAHUN 2019-2023) - Fortuna, Salsabilla Mutia; Eliza, Any; Nurmalia, Gustika (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2024)
This Study aims to test whetever there is an influence of Non-Performing Financing and Capital Adequacy Ratio, on Financial Sustainability Ratio. The population in this study is Islamic commercial banks in Indonesia that are registered with the OJK, namely there are 14 banks. The number of samples in this study is 9 samples bank with qualifications based on certain characteristic. The sampling technique uses the purposive sampling method. The research method used is quantitative with data sources in the form of secondary data. The data analysis method uses panel data sources in the form of secondary data. The result of this study provide empirical evidence  the Non-Performing Financing variable has no effect on the Financial Sustainability Ratio, but the Capital Adequacy Ratio has a significant positive effect on the Financial Sustainability Ratio. Simultaneously the variables Non Performing Financing and Capital Adequacy Ratio have a significant effect to the Financial Sustainability Ratio of Sharia Commercial Banks in Indonesia in 2019-2023.